Rancang Bangun Aplikasi Pengajuan Judul Skripsi Berbasis Mobile Hybrid Menggunakan Framework Ionic - Rayos Adyatma; Khairil Khairil; Indra Kanedi (Jurnal Media Infotama, 2026)
Mobile-based applications enable students and lecturers to access information and conduct various academic activities anytime and anywhere, as long as they are connected to the internet. This research aims to design and build a hybrid mobile-based thesis title submission application using the Ionic framework to simplify and expedite the process. The thesis title submission process in higher education is often still done manually, which is time-consuming, prone to administrative errors, and makes it difficult for students to monitor the application status. The system development method used is the Waterfall model, which includes needs analysis, design, implementation, testing, and maintenance. This application provides features for students to submit titles, view application status, and receive approval or rejection notifications from their supervisors. The supervisors can also accept, reject, or provide comments on the application. Test results indicate that the application runs well on the Android platform and is considered responsive and user-friendly by users. With this application, the thesis title submission process becomes more efficient, transparent, and digitally documented.